THE REVITALIZATION OF THE WEST PADEMAWU VILLAGE MARKET, BECOME A THEMATIC MARKET - Akh. FAWAID; Ali Wafa (Universitas Putera Batam, 2020)
The new village market that was built in Pademawu Barat Village, Pademawu District, is not yet fully able to compete with the traditional markets that were running earlier. The inability to compete, includes, the level of visits to the market is low, the income of market management is low, so that the people don't want to visit the village market. The Village Government prefers the important thing to build a physical market, rather than presentations on the future of the Village market. From these problems, researchers want to encourage the realization of thematic markets. As a result, the average community agreed that the market should be used as a thematic market. With the hope, the number of visitors can increase. The method in this research is to use a qualitative descriptive research method.